An ethnographic approach to strategy as practice: Using video to observe strategizing - LeBaron, Curtis (Henry Stewart Talks, 2012)
Ethnography in evolution for hundreds of years, Ethnography in stark contrast to psychology, Video Ethnography, Video analysis, Origins and influences, Conversation analysis, Harvey Sacks, Action as socially constitutive, Context analysis, Logo-centric conversation analysis, Proxemics, Kinesics, Procedures in video ethnography, Steps in a Microethnographic Study, Data collection, Boundary moments, Assumptions behind the research method, The cinematic features of the data, The story of the organization